Quadratic labor adjustment costs and the New-Keynesian model - Wolfgang Lechthaler; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2008)
We build quadratic labor adjustment costs into an otherwise standard New-Keynesian model of the business cycle and show that this is sufficient to increase both, output and inflation persistence.
More recent version: http://hdl.handle.net/10419/130554
Keywords: E24; E32; E52; J23; 330; monetary persistence; labor adjustment costs; Preisrigidität; Arbeitsmarkt; Anpassungskosten; Ungleichgewichtstheorie; Konjunkturtheorie; Theorie